1980
DOI: 10.2307/2006211
|View full text |Cite
|
Sign up to set email alerts
|

Outline of a Proof that Every Odd Perfect Number has at Least Eight Prime Factors

Abstract: Abstract.An argument is outlined which demonstrates that every odd perfect number is divisible by at least eight distinct primes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Brent, Cohen and Te Riele [4] have shown that there is no odd perfect number below 10^*"*. Moreover, Hagis [5] has shown (his announcement of this result [6] came a few years earlier in 1975) that an odd perfect number must have at least 8 prime factors. Furthermore, Heath-Brown [7] has shown that if n is an odd perfect number with at most k prime factors, then n < 4'\…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Brent, Cohen and Te Riele [4] have shown that there is no odd perfect number below 10^*"*. Moreover, Hagis [5] has shown (his announcement of this result [6] came a few years earlier in 1975) that an odd perfect number must have at least 8 prime factors. Furthermore, Heath-Brown [7] has shown that if n is an odd perfect number with at most k prime factors, then n < 4'\…”
Section: Resultsmentioning
confidence: 98%
“…> prevprime(\OO); 97 We can let Maple list for us the first 50 prime numbers: > s:=NULL: for i to 50 do s:=s,ithprime(i)od:s; 2, 3,5,7,11,13,17,19,23,29,31,37,41,43,47,53,59,61,67,71,73,79,83,89,97,101,103,107,109,113,127,131,137,139,149,151,157,163,167,173,179,181,191,193,197,199,211,223,227,229 Generating Bernoulli numbers:…”
mentioning
confidence: 99%
“…We note that the number of distinct prime factors (n) of an odd perfect number n is (n) 8 [2] (if 3 does not divide n, then (n) 11, [3,4]). A recent result of this kind is: if (n) = 8, then 5|n [8].…”
Section: By Mcdaniel and Hagis's Results We Can Assume Is Not Congruenmentioning
confidence: 99%
“…We now take & to be the smallest integer i for which (3) holds. Thus (4) and so, in the case k = r, we have…”
Section: A Preparatory Lemmamentioning
confidence: 97%
“…However it is known that there is no such number below 10 300 (see Brent[l]). Moreover it has been proved by Hagis [4] and Chein [2] independently that an odd perfect number must have at least 8 prime factors. In fact results of this latter type can in principle be obtained solely by calculation, in view of the result of Pomerance [6] who showed that if JV is an odd perfect number with at most k prime factors, then JV < (4&) (4 * )!!…”
Section: Introductionmentioning
confidence: 99%